Tensile bond strength of indirect composites luted with three new self-adhesive resin cements to dentin - (:unkn) unknown (UNIV SAO PAULO FAC ODONTOLOGIA BAURU, 2011)
Objective: The aims of this study were to evaluate the tensile bond strengths between indirect composites and dentin of 3 recently developed self-adhesive resin cements and to determine mode of failure by SEM. Material and Methods: Exposed dentin surfaces of 70 mandibular third molars were used. Teeth were randomly divided into 7 groups: Group 1 (control group): direct composite resin restoration (Alert) with etch-and-rinse adhesive system (Bond 1 primer/adhesive), Group 2: indirect composite restoration (Estenia) luted with a resin cement (Cement-It) combined with the same etch-and-rinse adhesive, Group 3: direct composite resin restoration with self-etch adhesive system (Nano-Bond), Group 4: indirect composite restoration luted with the resin cement combined with the same self-etch adhesive, Groups 5-7: indirect composite restoration luted with self-adhesive resin cements (RelyX Unicem, Maxcem, and Embrace WetBond, respectively) onto the non-pretreated dentin surfaces. Tensile bond strengths of groups were tested with a universal testing machine at a constant speed of 1 ririm/rnin using a 50 kgf load cell. Results were statistically analyzed by the Student's t-test. The failure modes of all groups were also evaluated. Results: The indirect composite restorations luted with the self-adhesive resin cements (groups 5-7) showed better results compared to the other groups (p<0.05). Group 4 showed the weakest bond strength (p>0.05). The surfaces of all debonded specimens showed evidence of both adhesive and cohesive failure. Conclusion: The new universal self-adhesive resins may be considered an alternative for luting indirect composite restorations onto non-pretreated dentin surfaces.
Keywords: Bond; Composite resin; Cementation; Dentin; IN-VITRO; LUTING AGENTS; RESTORATIVE MATERIALS; SHEAR; ENAMEL; SYSTEMS; MICROLEAKAGE; DEGRADATION; PERFORMANCE; ETCH